PALMD as a novel target for calcific aortic valve stenosis. (March 2019) - Bossé, Yohan; Mathieu, Patrick; Thériault, Sébastien
Abstract : Purpose of review: Novel medical treatments are urgently needed to stem the escalating socioeconomic burden of calcific aortic valve stenosis (CAVS). Herein, we describe the discovery of PALMD as a disease-causing gene for CAVS and discuss its implications for the understanding of disease pathogenesis and the development of new treatment options. Recent findings: Large-scale genomic approaches are finally starting to yield genetic loci robustly associated with CAVS. PALMD was discovered using a transcriptome-wide association study, whereby the results of a genome-wide association study were integrated with the first expression quantitative trait loci mapping study in human aortic valve tissues. The direction of effect indicated that the CAVS risk alleles at the PALMD locus conferred susceptibility by decreasing the mRNA expression levels of PALMD in valve tissues. Further analyses, along with our limited knowledge on the biology of this gene, suggested that PALMD is a noncoronary aortic disease gene specific for CAVS that is likely to mediate its effect through pathways involved in cardiac development and/or remodeling. Summary: Treatment modalities that increase the expression and/or function of PALMD in valve tissues must be evaluated. PALMD provides key insights into the genetics and pathogenesis of CAVS, will orient clinically relevant laboratory-based research and sets a turning point for gene discovery in CAVS.